2015
DOI: 10.1038/srep11382
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 does not require interscapular brown adipose tissue and improves liver metabolic profile in animal models of obesity and insulin-resistance

Abstract: FGF21 is a key metabolic regulator modulating physiological processes and its pharmacological administration improves metabolic profile in preclinical species and humans. We used native-FGF21 and a long-acting FGF21 (PF-05231023), to determine the contribution of liver and brown adipose tissue (BAT) towards metabolic improvements in Zucker rats and DIO mice (DIOs). FGF21 improved glucose tolerance and liver insulin sensitivity in Zuckers without affecting BW and improved liver function by decreased lipogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 40 publications
4
39
0
Order By: Relevance
“…Similar clamp data pertaining to glucose flux and glucose uptake were reported for lean and DIO mice infused with recombinant FGF21 for seven days [43]. In addition to clamp studies, assessment of tissue-specific glucose uptake by [ 18 F]-FDG/PET imaging in DIO mice revealed that brown adipose tissue, but not muscle, is a major site of glucose disposal following FGF21 administration for 2 weeks [44]. …”
Section: Metabolic Actions Of Fgf21mentioning
confidence: 56%
See 1 more Smart Citation
“…Similar clamp data pertaining to glucose flux and glucose uptake were reported for lean and DIO mice infused with recombinant FGF21 for seven days [43]. In addition to clamp studies, assessment of tissue-specific glucose uptake by [ 18 F]-FDG/PET imaging in DIO mice revealed that brown adipose tissue, but not muscle, is a major site of glucose disposal following FGF21 administration for 2 weeks [44]. …”
Section: Metabolic Actions Of Fgf21mentioning
confidence: 56%
“…In addition, the importance of brown adipose tissue in mediating the effects of FGF21 has been questioned due to maintenance of FGF21 efficacy in mice following the surgical excision of intrascapular brown adipose tissue [43,44] Together, these recent data suggest that adipose-mediated thermogenesis may not be responsible for the energy expending effects of FGF21. However, UCP1 KO mice have compensatory mechanisms of thermogenesis [61], and it is possible that FGF21-mediated increases in energy expenditure involve both UCP1-dependent and -independent mechanisms within adipose tissue.…”
Section: Metabolic Actions Of Fgf21mentioning
confidence: 99%
“…Long-term protein restriction significantly increased both UCP1 and Cidea mRNA within iWAT in association with morphological changes consistent with browning, and these effects were absent in FGF21-KO mice. Whether these effects on WAT and BAT are required for the persistent increase in EE and reduction in body weight gain observed with long-term dietary protein restriction remains unclear, as recent reports suggest that the effects of FGF21 on EE may not require UCP1 or WAT browning (Bernardo et al, 2015; Samms et al, 2015; Veniant et al, 2015), although UCP1 appears contribute to the metabolic effects induced by dietary restriction of just the amino acid methionine (Wanders et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The insulin sensitizing effects of FGF21 are adipose tissue dependent as shown by an inability of FGF21 to improve insulin sensitivity in lipodystrophic transgenic mice [41], [52]. In contrast, surgical resection of the interscaplar BAT does not abolish the response to FGF21-analogs, suggesting that small BAT depots distributed throughout the mouse may be sufficient to mediate the FGF21 effects in mouse [46], [51], [53], [54].…”
Section: Metabolic E昀fects In Obese Micementioning
confidence: 91%
“…A concomitant increase in uptake of glucose tracer into interscapular brown adipose tissue (BAT) as well an increase in resting core body temperature suggests that EE is predominantly driven by BAT thermogenesis [12], [13], [15], [16], [27], [51]. The insulin sensitizing effects of FGF21 are adipose tissue dependent as shown by an inability of FGF21 to improve insulin sensitivity in lipodystrophic transgenic mice [41], [52].…”
Section: Metabolic E昀fects In Obese Micementioning
confidence: 99%